Determinant Factors Effecting Poverty Among New Converts In Selangor, Malaysia - Fuadah Johari; Muhammad Ridhwan Ab. Aziz; Kalsom Abd Wahab; Ahmad Fahme Mohd Ali (Universiti Ar-Raniry, Acheh, Indonesia, 2024)
Volume: 4, No: 1